2001
DOI: 10.1093/hmg/10.3.243
|View full text |Cite
|
Sign up to set email alerts
|

Maternal sex chromosome non-disjunction: evidence for X chromosome-specific risk factors

Abstract: Human trisomy is attributable to many different mechanisms and the relative importance of each mechanism is highly chromosome specific. The association between altered recombination and maternal non-disjunction is well documented: reductions in recombination have been reported for maternal meiosis I (MI) errors involving chromosomes 15, 16, 18 and 21 and increased recombination has been reported for meiosis II (MII) errors involving chromosome 21. We therefore investigated maternal X chromosome non-disjunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 19 publications
4
42
0
2
Order By: Relevance
“…Interestingly, similar trend is also evident for chromosome 15, 18 and X chromosome (Robinson et al 1998;Thomas et al 2001;Bugge et al1998). This finding suggests two important possibilities.…”
Section: Susceptible Chiasma Formation and Its Interaction With Matersupporting
confidence: 61%
“…Interestingly, similar trend is also evident for chromosome 15, 18 and X chromosome (Robinson et al 1998;Thomas et al 2001;Bugge et al1998). This finding suggests two important possibilities.…”
Section: Susceptible Chiasma Formation and Its Interaction With Matersupporting
confidence: 61%
“…In the XXYs of paternal origin, there is again no effect of parental age, with the majority resulting from failure of recombination in the pairing region of the X and Y chromosomes followed by nondisjunction at the first meiotic division (49). In contrast, the XXYs of maternal origin are associated with advanced maternal age and a variety of unusual patterns of recombination in the first or second meiotic division (51). The great majority of XXX females, whether ascertained as spontaneous abortions or live births, are the result of nondisjunction of the maternal X chromosome, usually occurring at the first meiotic division.…”
Section: The Origin Of Numerical Chromosome Abnormalitiesmentioning
confidence: 99%
“…The great majority of XXX females, whether ascertained as spontaneous abortions or live births, are the result of nondisjunction of the maternal X chromosome, usually occurring at the first meiotic division. This is also associated with a marked increase in maternal age (51). XYY males are not found in excess among spontaneous fetal deaths, are not associated with an increase in paternal age, and are the result of fertilization of a 23,X oocyte by a sperm with an additional Y chromosome.…”
Section: The Origin Of Numerical Chromosome Abnormalitiesmentioning
confidence: 99%
“…4 Failure to recombine is also important in the genesis of 47,X M X M Y cases. Thomas et al 5 estimated that approximately 25% of these cases involve maternal meioses in which the two X chromosomes fail to pair and/or recombine with each other. However, Thomas et al 5 also observed another, curiously, abnormality of recombination in maternally derived cases.…”
Section: Cytogenetic Origin and Molecular Pathogenesismentioning
confidence: 99%
“…Thomas et al 5 estimated that approximately 25% of these cases involve maternal meioses in which the two X chromosomes fail to pair and/or recombine with each other. However, Thomas et al 5 also observed another, curiously, abnormality of recombination in maternally derived cases. A small proportion of cases appeared to recombine at, or extremely close to, the centromere-normally a "dead" spot for recombination.…”
Section: Cytogenetic Origin and Molecular Pathogenesismentioning
confidence: 99%